The benefits of iron supplementation following blood donation vary with baseline iron status. Issue 7 (15th April 2020) - Mast, Alan E.; Szabo, Aniko; Stone, Mars; Cable, Ritchard G.; Spencer, Bryan R.; Kiss, Joseph E.; ,
Abstract: Whole blood donation rapidly removes approximately 10% of a donor's blood volume and stimulates substantial changes in iron metabolism and erythropoiesis. We sought to identify donors who benefit from iron supplementation, describe the nature of the benefit, and define the time course for recovery from donation. Blood samples were collected over 24 weeks following whole blood donation from 193 participants, with 96 participants randomized to 37.5 mg daily oral iron. Changes in total body, red blood cell (RBC), and storage iron, hepcidin, erythropoietin, and reticulocyte count were modeled using semiparametric curves in a mixed model. and the changes were compared among six groups defined by baseline ferritin (<12; 12‐50; ≥50 ng/mL) and iron supplementation. The effect of oral iron on storage and RBC iron recovery was minimal in donors with baseline ferritin ≥50 ng/mL, but sizeable when ferritin was <50 ng/mL. Iron initially absorbed went to RBC and storage iron pools when ferritin was <12 ng/mL but went mostly to RBCs when ferritin was ≥12 ng/mL. Donors with ferritin ≥12 ng/mL had a "ripple" increase in reticulocytes 100 days after donation indicating physiological responses occur months following donation. Thus, iron supplements markedly enhance recovery from whole blood donation in donors with ferritin <50 ng/mL. However, full recovery from donation requires over 100 days when taking iron. The findings also highlight the value of the study of blood donors for understanding human hemoglobin and iron metabolism and their usefulness for future studies as additional biomarkers are discovered.